Noninferior red cell concentrate quality after repeated air rescue mission transport for prehospital transfusion - Böcker, Clemens; Sitzmann, Nicole; Halblaub Miranda, Jose Luis; Suhr, Hajo; Wiedemann, Philipp; Bieback, Karen; Rudolph, Marcus; Klüter, Harald (Transfusion medicine and hemotherapy, 2022)
Background: Transfusion of red cell concentrates (RCCs) is an integral therapy after severe hemorrhage or trauma. Prehospital transfusion offers an immediate intervention in emergency cases. Air ambulance-based prehospital transfusion, already used in different countries, is currently established in Germany. Limited information is available for regulatory-compliant transport logistics of RCCs and their quality after repeated air rescue missions. Thus, the aim of this study was (i) to validate regulatory-compliant logistics and (ii) to assess product quality, analyzing biochemical parameters and RBC morphology. Study Design and Methods: Due to regulatory requirements, we adapted a rotation system of 1 day transport, 1 day quarantine storage and 1 day storage over the entire RCC shelf life. RCCs transported on air rescue missions (flight group) were compared against a control group, treated identically except for helicopter transport. RCCs were visually inspected, and their temperature was documented throughout the entire rotation cycles. RCCs at the end of shelf life (end point samples) were assessed for levels of hemoglobin, hematocrit, free hemoglobin, hemolysis, mean corpuscular volume, potassium and pH. In addition, morphological changes were assessed using flow morphometry. Results: In total 81 RCCs were assessed in the flight group and 50 in the control group. Within the flight group, 30 RCCs were transfused. RCCs were dispatched on average 11 times (7-13 times). The average flight time was 18.3 h (6.6-28.8 h). The rotation system ensured adherence to regulatory guidelines, especially compliance to storage conditions of +2 to +6°C of intermediate storage. Biochemical and morphological quality parameters did not exhibit any changes upon repeated air rescue missions. A correlation with respect to the flight time was not observed either. Discussion: The quality of RCCs after repeated air rescue missions is noninferior to control samples regarding biochemical and morphological parameters. The product quality is within German regulations for up to 42 days of storage. The logistics and maintenance of the thermal conditions are safe and feasible. Thus, a rotation system of RCCs offers a regulatory-compliant option to supply air rescue missions with RCCs to allow life-saving prehospital transfusions at the incident scene.
Gesehen am 08.01.2024